Ο πατριάρχης Γρηγόριος ΣΤ' και η Καραμανλιδική μετάφραση της "Ορθόδοξης διδασκαλίας" του Πλάτωνος Μόσχας από τον Παΐσιο Καισαρείας - Μαμώνη, Κυριακή (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1988)
The author discusses the Patriarchal manuscript code 204(320) now deposited in the General State Archives in Athens. This code as well as code 69 of the Benaki Museum, refer to the establishment of the «Central Patriarchal Committee of Constantinople» by Patriarch Gregory VI and its activity in the years 1836-1839 and 1846. Among the contents of code 204 of special interest is the patriarchal criticism of the Karamanli edition of the «Orthodox Catechism» originally composed by the Metropolitan of Moscow Plato and translated by Paisius, Metropolitan of Caesarea, for the spiritual needs of his Turkish-speaking flock in the interior of Asia Minor (Cappadocia). Paisius’s intention in issuing the translation was to counter the prosyletizing activities of Protestant missionaries among his flock. From the evidence of the code the following interesting conclusion can be drawn: since 1836 the Patriarchate of Constantinople censored not only the publications of the Protestant missionaries but also works by Orthodox authors, writing in defence of the Orthodox faith. The case of Metropolitan Paisius is a characteristic one. Though he was a close collaborator of the Patriarch and also a senior prelate noted for his devotion to his pastoral duties, he did not avoid the severity of patriarchal censorship to which he had to answer for his translation.